Peripheral Arterial Disease in Chronic Kidney Disease Patient - Hamid, Md Abdul; Paul, Sujat; Dutta, Pradip Kumar (Journal of Chittagong Medical College Teachers’ Association, 2018)
Among the different complications of chronic kidney diseases, Peripheral Arterial Disease (PAD) is not uncommon which is an indicator of wide spread atherosclerosis in other vascular territories, such as the cerebral and coronary circulations. Traditional cardiovascular risk factors, such as black race, male gender, age,tobacco use, diabetes, hyperlipidemia, and hypertension are also associated with PAD. But in kidney patients this disease is sometimes neglected. This present review tends to describe epidemiology, risk factors and necessities for screening of PAD in chronic kidney disease patients. JCMCTA 2017 ; 28 (2) : 3-11